Sodium ion battery with sodium nitrate as positive electrode functional additive

By introducing sodium nitrate and Cu2+ into the positive electrode of sodium ion battery, regulating the ion concentration of Cu2+ and NO3-, the problems of interface mask density and electrochemical performance of sodium ion battery in ester electrolyte are solved, and the battery is realized The construction of stable interface mask and improves electrochemical performance.

CN119400871APending Publication Date: 2025-02-07LIYANG HINA BATTERY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411572930.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

When existing sodium ion batteries use sodium nitrate as the positive electrode additive in ester electrolytes, there are problems such as low density, poor ion conduction ability, poor antioxidant performance, and fast internal resistance growth, making it difficult to build a stable interface mask.

Method used

By introducing sodium nitrate as an additive in the positive electrode sheet and using positive electrode active materials that are suitable for Cu2+ dissolution ability, Cu2+ is introduced into the electrolyte to regulate the ion concentration of Cu2+ and NO3- to achieve the cycle life and high temperature fullness of the battery Performance improvements in electrical storage and other aspects.

Benefits of technology

It has achieved excellent results in the construction of stable interface masks and improving electrochemical performance, improved circulation and rate performance, and delayed the growth of the storage internal resistance of the positive electrode material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005120993200000091
    Figure BDA0005120993200000091
  • Figure BDA0005120993200000111
    Figure BDA0005120993200000111
  • Figure BDA0005120993200000121
    Figure BDA0005120993200000121
Patent Text Reader

Abstract

The invention relates to a sodium ion battery with sodium nitrate as a positive electrode functional additive, a copper-containing layered oxide is adopted as a positive electrode active material, an electrolyte containing an ester solvent is adopted, the concentration n of Cu < 2 + > in the electrolyte is more than 1ppm and less than or equal to 300ppm, and the ratio N of the amount of substance of Cu < 2 + > to NO3 <-> in the electrolyte is more than or equal to 0.01 and less than or equal to 0.2. According to the invention, NaNO3 is introduced into the sodium-ion battery through the positive electrode, so that the electrochemical performance of the sodium-ion battery is improved, and meanwhile, the internal resistance increase of high-temperature full-electricity storage of a battery cell is particularly delayed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to an application of a sodium ion battery using sodium nitrate as a positive electrode additive and a preparation method thereof. Background Art

[0002] Sodium-ion batteries have similar working principles to lithium-ion batteries, and have abundant sodium resources, as well as excellent low-temperature and rate performance, so they have the potential for large-scale application. At present, there is room for further improvement in the cycle life and energy density of sodium-ion batteries, and the construction of excellent solid electrolyte interface membranes is very critical.

[0003] Constructing an effective and stable interface film (CEI) on the positive electrode side can effectively prevent side reactions between the positive electrode and the electrolyte, inhibit the dissolution of transition metals, and thus help improve the electrochemical performance of the battery. However, due to the specific environment of high voltage and high energy on the positive electrode side, the construction of CEI films often has undesirable problems such as low density, poor ion conductivity, poor antioxidant performance, and rapid internal resistance growth.

[0004] NaNO3 is one of the additives that is expected to assist in the construction of CEI membranes at the positive electrode. However, studies have found that NaNO3 has good solubility in systems containing ether solvents. However, ether solvents have poor antioxidant properties, which makes it difficult to use in batteries with high-voltage positive electrode materials. Ester electrolytes have a wider electrochemical window and better high-temperature performance, but the solubility of NaNO3 additives in ester solvents is low. It is difficult for NaNO3 to form a dense and strong interface film in ester solvent systems, and the internal resistance of full-charge storage also has a large increase and deterioration due to the unstable existence of the CEI membrane. Therefore, exploring the improvement of the solubility of NaNO3 in ester electrolytes so that it can effectively play a role in the reconstruction and construction process of the CEI membrane at the positive electrode is of great significance to improving the high-voltage and antioxidant capabilities of the CEI membrane and improving the problem of internal resistance growth while improving the side reactions and ion dissolution problems at the positive electrode.

[0005] To this end, this application is filed. Summary of the invention

[0006] In view of the above problems of the prior art, the present invention introduces sodium nitrate (NaNO3) as an additive into the positive electrode sheet, and at the same time selects a Cu 2+ The dissolution capacity of the positive electrode active material is introduced into the electrolyte. 2+ , effectively regulating the Cu in the sodium ion battery system 2+ and NO3 - The combination of ion concentrations achieves improved battery performance in terms of cycle life, high-temperature full-charge storage, etc.

[0007] Specifically, the present invention provides a sodium ion battery with sodium nitrate as a positive electrode functional additive, comprising a positive electrode, a negative electrode, an electrolyte and a separator; the positive electrode contains the functional additive sodium nitrate, and the positive electrode active material is a copper-containing layered oxide Na n Cu u M v Ni x Mn y Fe z O2, 0.9≤n≤1.1, 0.05≤u≤0.15, 0≤v≤0.05, 0.1≤x≤0.25, 0.3≤y≤0.4, 0.3≤z≤0.4, 0.9≤u+v+x+y+z≤1.1, M is selected from one or more of Mg, Ca, B, Al, Zr, Ti, W, Mo, Cr, Sr, Y, Cd, Sn, Sb, Ce, Li, K and Ag; an electrolyte containing an ester solvent is used, and the Cu in the electrolyte is 2+ The concentration n satisfies 1ppm<n≤300ppm, and the Cu 2+ and NO3 - The amount ratio N of the substances satisfies 0.01≤N≤0.2.

[0008] In some embodiments, the sodium nitrate forms an inorganic Na-N SEI film in situ on the negative electrode sheet, wherein the inorganic Na-N SEI film has Na3N and NaN x O y .

[0009] In some embodiments, the Cu in the electrolyte 2+ The concentration n satisfies 30ppm<n≤200ppm.

[0010] In some embodiments, the electrolyte contains Cu 2+ and NO3 - The amount ratio N of the substances satisfies 0.01≤N≤0.1.

[0011] In some embodiments, the Cu 2+ It also comes from the electrolyte.

[0012] In some embodiments, the Cu 2+ It also comes from copper ion additives in the electrolyte.

[0013] In some embodiments, the copper ion-containing additive includes one or more of CuF2, CuFSI, and copper hexafluorophosphate.

[0014] In some embodiments, the ester solvent in the electrolyte containing the ester solvent includes one or more of ethylene carbonate, ethylene carbonate, propylene carbonate, dipropyl carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, methylpropyl carbonate, ethylpropyl carbonate, butylene carbonate, methyl formate, ethyl acetate, propyl acetate, propyl propionate, methyl butyrate, ethyl propionate, ethyl butyrate, etc.

[0015] In some embodiments, the average particle size of the sodium nitrate does not exceed 2 μm, preferably 10 nm ≤ D ≤ 1 μm.

[0016] In some embodiments, the mass percentage of sodium nitrate in the positive electrode dissolved in the electrolyte is 0.05% to 0.75%.

[0017] In some embodiments, sodium nitrate is used as a positive electrode functional additive, and its mass proportion in the positive electrode slurry is 0.1 to 1.5 wt%.

[0018] The present invention also provides a method for preparing the above-mentioned sodium ion battery, using a copper-containing layered oxide as a positive electrode active material, and adding sodium nitrate to the positive electrode slurry according to a stoichiometric ratio to prepare a positive electrode plate, adding a negative electrode plate and a separator, and injecting an electrolyte to assemble a battery, and performing battery formation.

[0019] Compared with the prior art, the present invention has at least the following beneficial effects:

[0020] The present invention fully studies the introduction of copper ions (Cu 2+ ) to improve the solubility of sodium nitrate in the electrolyte containing ester solvents, and by precisely controlling the sodium nitrate and Cu in the positive electrode sheet 2+ The dosage achieves the excellent effect of sodium ion battery in stabilizing the interface film construction and improving the electrochemical performance. The gradually dissolved NaNO3 additive can not only promote the in-situ construction of Na-N inorganic SEI film at the negative electrode, but also improve the cycle and rate performance. In particular, as the sodium nitrate in the positive electrode sheet is gradually dissolved, a small amount of NO3 will exist near the positive electrode side. - , NO3 - The presence of anions will break the original solvation structure and affect the Na + The desolvation process causes the CEI membrane close to the positive electrode to generate more inorganic components, making it dense, strong and not easy to dissolve, thereby improving the oxidation stability.

[0021] The present invention provides a new idea for constructing a stable interface film for a sodium ion battery with a high voltage positive electrode system, and at the same time has great significance for the promotion and application of sodium nitrate in sodium ion batteries with an ester solvent system. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0023] Figure 1 This is a comparison chart of the precipitation conditions before and after adding CuF2 after adding 1000ppm NaNO3 to the ester electrolyte (PC / DMC) of the present invention. Among them, A is before adding CuF2, and B is after adding CuF2.

[0024] Figure 2 In Example 1 of the present invention, Na-N inorganic (Na3N and NaN x O y )XPS of SEI film.

[0025] Figure 3 This is the principle of the present invention that NaNO3 changes the solvation structure during the process of participating in the construction of the CEI membrane at the positive electrode. DETAILED DESCRIPTION

[0026] The embodiments of the present invention are only a part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

[0027] At present, sodium nitrate is used as an additive, mostly as a salt additive added to the electrolyte to improve the safety and stability of the electrolyte. At the same time, as a sodium ion supplement, it can also improve the overall performance of sodium ion batteries. The nitrate in sodium nitrate is a large anion with a large proton donor capacity (Donor number), which results in the inability to effectively stabilize and solvate the sodium ions in sodium nitrate in most solvents, especially ester electrolytes. This not only affects the solubility of sodium nitrate, but also brings about problems such as uneven distribution of sodium nitrate and abnormal deposition, which often prevents sodium nitrate from playing its due role in the electrolyte.

[0028] The applicant found that by adding a copper source to the battery system, the copper ions (Cu 2+ ), and precisely regulate the sodium nitrate and Cu 2+ The dosage is beneficial to improve the solubility of sodium nitrate and promote the stability of the battery system.

[0029] The invention provides a sodium ion battery using sodium nitrate as a positive electrode functional additive, comprising a positive electrode, a negative electrode, an electrolyte and a separator; the positive electrode contains the functional additive sodium nitrate, and the positive electrode active material is a copper-containing layered oxide Nan Cu u M v Ni x Mn y Fe z O2, 0.9≤n≤1.1, 0.05≤u≤0.15, 0≤v≤0.05, 0.1≤x≤0.25, 0.3≤y≤0.4, 0.3≤z≤0.4, 0.9≤u+v+x+y+z≤1.1, M is selected from one or more of Mg, Ca, B, Al, Zr, Ti, W, Mo, Cr, Sr, Y, Cd, Sn, Sb, Ce, Li, K and Ag; an electrolyte containing an ester solvent is used, and the Cu in the electrolyte is 2+ The concentration n satisfies 1ppm<n≤300ppm, and the Cu 2+ and NO3 - The amount ratio N of the substances satisfies 0.01≤N≤0.2.

[0030] Cu 2+ Than Na + The charge is high and the radius difference is not large. When Cu 2+ The applicant found that a very small amount of Cu 2+ It can promote the NO3 - Coordinate to form Cu 2+ -NO3 - complex, resulting in Na-NO3 - The bond breaks, so Cu 2+ -NO3 - Complex and Na + -solvent (such as PC / DEC) complexes can be dissolved in ester solvents to form a new dissolution structure and form Na-N inorganic (Na3N and NaN) in situ on the negative electrode during the formation or cycle process. x O y , where x and y satisfy the stoichiometric ratio according to the element valence) SEI film (such as Figure 2 ), thus making the sodium ion battery have higher interfacial stability. 2+ In the electrolyte containing ester solvents of sodium ion batteries, it shows stronger electron-withdrawing ability, which can produce a desheathing effect on the coordinated solvent molecules, making Cu 2+ With NO3 - The interaction between + With NO3 - The interaction between them promotes the formation of Cu 2+ -NO3 - complex, which also explains the 2+ Under the solubilization condition, NaNO3 has a greater degree of solubility in ester solvents.2+ The effect of the presence of on the solubility of NaNO3 in ester solvents, such as Figure 1 As shown, the applicant directly added excess NaNO3 to the ester electrolyte, and a precipitate was clearly seen at the bottom, indicating that NaNO3 was almost insoluble; but when a certain amount of CuF2 was added, the precipitate at the bottom of the electrolyte disappeared.

[0031] Cu 2+ In the sodium ion battery system, there can be many sources, such as dissolution from the inherent components of the positive electrode active material, or directly present in the electrolyte in the form of copper ion additives, or in the negative electrode or separator in the form of copper ion additives. The applicant found that higher concentrations of Cu 2+ Although it can promote the dissolution of more NaNO3, it will also catalyze the decomposition of the electrolyte, which is not conducive to the stability of the system. 2+ The concentration does not significantly reduce the effect of promoting the dissolution of NaNO3 and forming the Na-N inorganic film in situ. 2+ The concentration is controlled at an extremely low level of 1ppm<n≤300ppm, and preferably 30ppm<n≤200ppm.

[0032] In the present invention, the Cu in the electrolyte 2+ The source includes at least the copper-containing layered oxide Na n Cu u M v Ni x Mn y Fe z O2, NaNO3 in the electrolyte comes from the sodium nitrate additive in the positive electrode. n Cu u M v Ni x Mn y Fe z O2 as Cu 2+ When it is the only source of Cu in the electrolyte, copper, as one of the components of the layered oxide material, will dissolve in a very small amount in the electrolyte, which can provide 2+ The concentration n satisfies the range of 10ppm≤n≤150ppm. And NaNO3 is added to the positive electrode slurry in the form of an additive and serves as NO3 in the electrolyte. -When it is the only source of sodium nitrate, the amount of sodium nitrate dissolved in the electrolyte and the amount of sodium nitrate additive added in the positive electrode under the same conditions also have a general trend of being basically proportional. The proportion of sodium nitrate in the electrolyte can be regulated by reasonably adjusting the amount of sodium nitrate additive added in the positive electrode to achieve the target proportion requirement (so that the mass proportion of NaNO3 in the electrolyte meets 0.05% to 0.75%). We found that within the general loading range of the positive electrode slurry, by controlling the average particle size of sodium nitrate not to exceed 2μm, when the mass proportion of NaNO3 in the positive electrode slurry is 0.1-1.5wt%, the sodium nitrate dissolved in the electrolyte can meet the above target proportion requirements, so that the concentration of sodium nitrate dissolved in the electrolyte reaches about 500-8000ppm. NaNO3 from the positive electrode source constructs a Na-N inorganic SEI film in situ at the negative electrode through ion migration, improving the cycle and rate performance. At the same time, we also found that sodium nitrate additives from the positive electrode source also have an improvement effect on reducing the storage internal resistance growth rate of the battery. The possible reason is that Cu from the positive electrode 2+ By rapidly promoting the dissolution of NaNO3 from the positive electrode, part of the NO3 - The solvation structure on the positive electrode side is changed, so that the CEI on the positive electrode side is rich in inorganic components during the construction process, and is dense and strong, further improving the oxidation stability. Therefore, the sodium nitrate additive from the positive electrode accelerates the construction rate of the positive electrode interface film and promotes the construction of a tighter interface film on the positive electrode, which helps to improve the storage stability of the positive electrode active material, reduce the generation rate of residual alkali, and effectively delay the growth of the high-temperature full-charge storage internal resistance of the battery cell.

[0033] Cu 2+ The concentration in the electrolyte can be further controlled by a variety of other means and aspects. For example, when the copper-containing layered oxide is dissolved due to special systems such as additional coating or addition of complexing agents, 2+ When the dissolution into the electrolyte is insufficient, a supplementary copper source may be used, for example, by adding a soluble copper ion-containing additive to the electrolyte.

[0034] In Cu 2+ In the presence of, sodium nitrate can achieve higher solubility in the electrolyte and obtain a higher proportion. It should be pointed out that the higher the content of sodium nitrate in the electrolyte is, the better. Dissolving too much sodium nitrate will also bring about problems such as too thick interface film and hinder ion transmission. It is only because of the low solubility of sodium nitrate that the problem of insufficient interface film construction is more prominent. In the present invention, the solubility of sodium nitrate is no longer a limitation, so that the content range of sodium nitrate in the electrolyte can also be optimized and regulated (0.01≤N≤0.2). As a further preferred embodiment, Cu can be obtained when 0.01≤N≤0.1 2+ and NO3 -The better the match, the better the performance improvement.

[0035] Sodium nitrate added to the positive electrode can be 2+ In the presence of, it dissolves into the electrolyte. The concentration of sodium nitrate in the electrolyte (i.e., the concentration of NO3 - The concentration of sodium nitrate can be regulated by various means and aspects, including controlling the amount of sodium nitrate added as an additive in the system; and adjusting the particle size of sodium nitrate so that sodium nitrate can be more fully dissolved in the electrolyte; etc.

[0036] In the above-mentioned sodium ion battery system, the construction of other materials and systems is not particularly limited and can be implemented within the scope of general designs that have been successfully implemented in the field. In addition, if there is no conflict, the designs in the above-mentioned different sodium ion battery systems can also be cross- or superimposed.

[0037] As some alternatives, Cu in Na-ion batteries 2+ When it is derived from a copper ion-containing additive, CuF2, CuFSI, copper hexafluorophosphate, etc. can be used. The copper ion-containing additive generally has good solubility properties, and can be directly added to the electrolyte to basically achieve complete dissolution to control its concentration in the electrolyte.

[0038] As some optional options, the types of negative electrode active materials are not limited, including hard carbon, soft carbon and amorphous carbon, silicon-based materials, tin-based alloy materials, transition metal oxides, metal sulfides, phosphides, titanium-based materials, metal organic framework compounds and bio-based materials, etc.

[0039] As some optional schemes, the positive electrode and the negative electrode of the sodium ion battery also independently include a conductive agent and a binder. The conductive agent includes carbon nanotubes, graphene, carbon black, graphite, metal or metal oxide nanoparticles (such as silver, titanate, etc.), conductive polymers (such as polyaniline, polythiophene, etc.), organic conductive agents (such as acetylene black, etc.). Binders include polyvinylidene fluoride, polytetrafluoroethylene, polyimide, polyvinyl alcohol, styrene-butadiene rubber, sodium alginate, acrylic copolymers and polyurethane, etc.

[0040] As some optional schemes, the positive and negative electrodes of the sodium ion battery may also optionally add a thickener, such as sodium carboxymethyl cellulose CMC; the positive and negative electrode slurries may be either aqueous slurries, such as stirred in deionized water, or oil-based slurries, such as stirred in NMP.

[0041] As some optional schemes, the electrolyte contains an ester solvent, the ester solvent includes one or more of ethylene carbonate, ethylene carbonate, propylene carbonate, dipropyl carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, methyl formate, ethyl acetate, propyl acetate, propyl propionate, methyl butyrate, ethyl propionate, ethyl butyrate, etc.

[0042] As some optional schemes, the electrolyte containing ester solvents also includes sodium salt and additives. Sodium salt includes sodium hexafluorophosphate NaPF6, sodium bisfluorosulfonyl imide NaFSI, sodium bis(trifluoromethylsulfonyl)imide NaTFSI, sodium trifluoromethanesulfonate NaOTf, sodium tetrafluoroborate NaBF4, sodium bisoxalate borate NaBOB, sodium difluorooxalate borate NaDFOB, sodium perchlorate NaCIO4 or more. Additives include: one of unsaturated carbonate additives, fluorine-containing additives, sulfur-containing additives, silicon-containing additives and phosphorus-containing additives, preferably vinyl sulfate, fluoroethylene carbonate (FEC), bisfluoroethylene carbonate, vinylene carbonate, 1,3-propane sultone, 1-propylene-1,3-sultone, methane disulfonic acid methylene ester, tris(trimethylsilyl) phosphate and tris(trimethylsilyl) phosphite or tris(trimethylsilyl) borate at least one.

[0043] As some optional schemes, the base film of the diaphragm is a polyolefin film, which can be one or more of polypropylene (PP), polyethylene (PE), polyvinylidene fluoride (PVDF), cellulose, and can be a single layer or a multi-layer one.

[0044] As some optional solutions, the base film is further coated and / or impregnated with an adhesive, such as a PVDF coating, to attach other functional layers to the base film.

[0045] As some optional solutions, other functional layers on the diaphragm can be ceramic particle layers, which are beneficial to improve the heat resistance of the diaphragm and enhance the puncture resistance of the diaphragm.

[0046] As some optional options, sodium nitrate can be used as an additive, and the average particle size of the raw material particles should preferably satisfy 10nm≤D≤1μm, which is beneficial to improving the dissolution efficiency of NaNO3 and reducing local unevenness problems.

[0047] For sodium ion batteries using sodium nitrate as a positive electrode functional additive, sodium nitrate can be directly added to the positive electrode slurry according to a stoichiometric ratio, and then the electrode sheet is prepared according to the general preparation method of the electrode sheet, wherein the positive electrode uses a copper-containing layered oxide as the positive electrode active material. It is also preferred that sodium nitrate is first added to a solvent and fully dispersed to obtain a mixed solution, and then the mixed solution is mixed with the positive electrode raw material according to a stoichiometric ratio to prepare a positive electrode slurry, and then the electrode sheet is prepared according to the general preparation method of the electrode sheet, wherein the positive electrode uses a copper-containing layered oxide as the positive electrode active material. The pre-dispersed sodium nitrate ensures the uniformity of the sodium nitrate in the slurry, which is conducive to the construction of a stable SEI / CEI film. Other general preparation methods of sodium ion batteries can be used.

[0048] As some optional solutions, copper ion-containing additives may be added to the electrolyte and / or the positive electrode / negative electrode slurry according to a stoichiometric ratio.

[0049] The scheme of the present invention is further described in detail below through specific embodiments. The chemical raw materials involved in the embodiments of the present invention are all prior art and are all commercially available. The experimental devices, test devices, etc. involved in the following embodiments and comparative examples are all conventional devices in the art, without special requirements and limitations.

[0050] 1. Sodium ion battery with sodium nitrate as negative electrode functional additive

[0051] Embodiment 1:

[0052] Preparation of negative electrode sheets: (1) Add NaNO3 additive to deionized water, stir and ultrasonicate to obtain a uniform solution, wherein the average particle size of NaNO3 is 500nm; (2) Mix hard carbon, conductive agent (Super P), sodium carboxymethyl cellulose (CMC), and binder (SBR) in a mass ratio of 94:2:1.5:2.5, add deionized water and mix and stir evenly at a certain speed; (3) Add the mixed solution obtained in step (1) to the slurry of step (2) and stir evenly, stir at a certain speed for 20 minutes, adjust to a suitable viscosity, adjust the mass proportion of NaNO3 in the negative electrode slurry to 0.8wt%, then discharge the material, coat it on aluminum foil, and then dry, cold press, and cut to obtain negative electrode sheets;

[0053] Preparation of positive electrode: (1) NaCu 1 / 9 Ni 2 / 9 Fe 1 / 3 Mn 1 / 3The O2 positive electrode material, conductive agent Super P, conductive agent CNT, and binder PVDF are dissolved in the solvent NMP according to the mass ratio of 96.5:1.5:0.5:1.5, and stirred evenly at a certain speed. After adjusting to a suitable viscosity, the positive electrode slurry is coated on the aluminum foil; then the positive electrode sheet is obtained through drying, cold pressing, and slitting;

[0054] Preparation of electrolyte: First, mix PC / DEC to obtain an organic solvent, then dissolve sodium salt NaPF6 in the above solvent, then add electrolyte additive FEC and mix evenly to obtain sodium electrolyte;

[0055] The obtained positive electrode sheet, negative electrode sheet and separator are stacked in sequence and assembled to obtain a soft-pack battery.

[0056] Embodiment 2-7:

[0057] By changing some parameters in Example 1, the soft pack battery was prepared in the same manner as in Example 1. The positive electrode active material in Examples 6-7 was NaNi without Cu. 1 / 3 Fe 1 / 3 Mn 1 / 3 O2, and CuF2 was added to the electrolyte. The parameter changes and results are listed in Table 1.

[0058] Comparative Examples 1-5

[0059] By changing some parameters in Example 1, the soft pack battery was prepared in the same manner as in Example 1; wherein the positive electrode active material in Comparative Example 3 was NaNi without Cu. 1 / 3 Fe 1 / 3 Mn 1 / 3 O2, and no Cu is introduced into the system; the positive electrode active material in Comparative Example 4 uses NaNi without Cu 1 / 3 Fe 1 / 3 Mn 1 / 3 O2, and CuF2 is added to the electrolyte; the positive electrode active materials CuO and NaNi in Comparative Example 5 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 was compounded at a ratio of 1:9. The parameter changes and results are listed in Table 1.

[0060] Table 1 lists the electrochemical performance test results of each embodiment and comparative example. Among them, the specific operation of the 45°C cycle performance test is: at 45°C, charge the above battery at a constant current of 0.5C to 4.15V, and then discharge it at a constant current of 1C to 2V, and record the number of cycles corresponding to the capacity decay to 80% SOH. The -20°C charge and discharge test operation is: charge to full charge at room temperature 25°C, discharge at -20°C, and record the discharge amount. The 3C rate discharge test operation is: 0.5C charge and 3C discharge, cycle 50 times in the voltage range of 2.0-4.15V, and record the capacity retention rate. Tables 2 and 3 use the same test methods and conditions. Cu 2+ and NO3 - The mass percentage (ppm) in the electrolyte is measured by spectrophotometry after the battery is disassembled and tested.

[0061] Table 1

[0062]

[0063] It can be seen from Table 1 that, as shown in Examples 1-7, the Cu in the electrolyte 2+ The extremely low concentration requirement is met, and sodium nitrate is added to the negative electrode in a regulated amount to meet the Cu content in the electrolyte. 2+ and NO3 - When the amount ratio N of the substance satisfies 0.01≤N≤0.2, the cycle performance, low temperature charge and discharge, and rate (fast charge) performance of the battery are significantly optimized. 2+ By NaCu 1 / 9 Ni 2 / 9 Fe 1 / 3 Mn 1 / 3 O2 positive electrode material was introduced, and it was found that Cu dissolved in the electrolyte 2+ The concentration is about tens to more than one hundred ppm; Examples 6-7 respectively use the method of directly adding a limited concentration of CuF2 into the electrolyte; different methods of introducing a limited concentration range of Cu 2+ The performance improvement results are basically the same.

[0064] In Comparative Example 1, an excessive amount of sodium nitrate was introduced into the system, and in Comparative Example 2, the sodium nitrate material with a larger particle size was introduced. It can be seen that the performance improvement was not ideal. 2+ The presence of sodium nitrate can still be completely dissolved, but excessive sodium nitrate leads to a thick SEI film and more adverse side reactions. 2+ and NO3 - The concentration matching of is unbalanced, which affects the establishment of a uniform and stable interface film. 2+, resulting in sodium nitrate being almost unable to fully dissolve and establish an interface film, and at the same time being deposited in the system, resulting in a significant reduction in battery performance. In Comparative Example 4, excessive CuF2 was directly added to the electrolyte, and in Comparative Example 5, Cu was introduced into the positive electrode material in the form of CuO, both of which increased the Cu content in the electrolyte. 2+ The concentration is greatly increased, and the excess Cu 2+ It catalyzes the decomposition of the electrolyte and makes it difficult to achieve performance improvements.

[0065] 2. Sodium ion battery with sodium nitrate as positive electrode functional additive

[0066] Embodiment 8:

[0067] Preparation of negative electrode sheet: (1) hard carbon, conductive agent (Super P), sodium carboxymethyl cellulose (CMC), and binder (SBR) are mixed in a mass ratio of 94:2:1.5:2.5, deionized water is added, and the mixture is stirred evenly at a certain speed, and then adjusted to a suitable viscosity, and then discharged, coated on aluminum foil, and then dried, cold pressed, and cut to obtain a negative electrode sheet;

[0068] Preparation of positive electrode: (1) Add NaNO3 additive to deionized water, stir and ultrasonicate to obtain a uniform solution, wherein the average particle size of NaNO3 is 500nm; (2) Add NaCu 1 / 9 Ni 2 / 9 Fe 1 / 3 Mn 1 / 3 The O2 positive electrode material, the conductive agent Super P, the conductive agent CNT, and the binder PVDF are dissolved in the solvent NMP according to the mass ratio of 96.5:1.5:0.5:1.5, and stirred evenly at a certain speed; (3) the mixed solution obtained in step (1) is added to the slurry of step (2) and stirred evenly, and stirred at a certain speed for 20 minutes. After adjusting to a suitable viscosity, the mass proportion of NaNO3 in the positive electrode slurry is adjusted to 0.8wt%, and then the obtained positive electrode slurry is coated on aluminum foil; and then the positive electrode sheet is obtained after drying, cold pressing, and slitting;

[0069] Preparation of electrolyte: First, mix PC / DEC to obtain an organic solvent, then dissolve sodium salt NaPF6 in the above solvent, then add electrolyte additive FEC and mix evenly to obtain sodium electrolyte;

[0070] The obtained positive electrode sheet, negative electrode sheet and separator are stacked in sequence and assembled to obtain a soft-pack battery.

[0071] Embodiment 9-14:

[0072] By changing some parameters in Example 8, the remaining parameters were prepared in the same manner as in Example 8. In particular, the positive electrode active material in Examples 13-14 was NaNi free of Cu. 1 / 3 Fe 1 / 3 Mn 1 / 3 O2, and CuF2 was added to the electrolyte. The parameter changes and results are listed in Table 2.

[0073] Comparative Examples 6-10

[0074] By changing some parameters in Example 1, the soft pack battery was prepared in the same manner as in Example 1; wherein the positive electrode active material in Comparative Example 8 was NaNi free of Cu. 1 / 3 Fe 1 / 3 Mn 1 / 3 O2, and no Cu is introduced into the system; the positive electrode active material in Comparative Example 9 uses NaNi without Cu 1 / 3 Fe 1 / 3 Mn 1 / 3 O2, and CuF2 is added to the electrolyte; the positive electrode active materials CuO and NaNi in Comparative Example 10 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 was compounded at a ratio of 1:9. The parameter changes and results are listed in Table 2.

[0075] The specific operation of the 60℃ full-charge storage test is as follows: charge to 4.15V, record the initial internal resistance, store in a 60℃ oven for 30D, take out of the oven and let it cool to room temperature before recording the internal resistance.

[0076] Table 2

[0077]

[0078]

[0079] As can be seen from Table 2, as shown in Examples 8-14, under the same conditions, the introduction of sodium nitrate as a positive electrode functional additive also shows good electrical performance improvement ability relative to that as a negative electrode functional additive, and the trend of the cycle results is basically consistent with that of Examples 1-7. At the same time, it is also found that in terms of the overall effect of improving the cycle performance, although Examples 8-14 are slightly lower than Examples 1-7, sodium nitrate as a positive electrode functional additive also significantly improves the internal resistance growth of 30D stored at 60°C full charge, indicating that the direct introduction of sodium nitrate into the positive electrode can also construct an SEI film in situ at the negative electrode through ion migration, improve the cycle performance, and at the same time, the introduction of the positive electrode promotes the rate and density of the construction of the positive electrode CEI film, thereby delaying the growth of the storage internal resistance of the positive electrode material. Figure 3The effect of NaNO3 in the cathode slurry on the construction of CEI membrane is demonstrated. Since NaNO3 is gradually dissolved, there is a small amount of NO3 near the cathode side. - , NO3 - The presence of anions breaks the original solvation structure and changes the effect on Na + The desolvation process causes the CEI membrane close to the electrode side to generate more inorganic components, thereby improving the oxidation stability.

[0080] In Comparative Example 6, an excessive amount of sodium nitrate was introduced into the system, and in Comparative Example 7, the sodium nitrate material with a larger particle size was introduced, and the performance improvement was also unsatisfactory. 2+ , the battery performance is greatly reduced. Comparative Examples 9 and 10 both make Cu 2+ The above comparative examples 6-10 have similar effects to comparative examples 1-5, and similarly, performance improvement is difficult to achieve.

[0081] 3. Sodium nitrate as a sodium ion battery with diaphragm functional additive

[0082] Embodiment 15:

[0083] Preparation of negative electrode sheet: (1) hard carbon, conductive agent (Super P), sodium carboxymethyl cellulose (CMC), and binder (SBR) are mixed in a mass ratio of 94:2:1.5:2.5, deionized water is added, and the mixture is stirred evenly at a certain speed, and then adjusted to a suitable viscosity, and then discharged, coated on aluminum foil, and then dried, cold pressed, and cut to obtain a negative electrode sheet;

[0084] Preparation of positive electrode: (1) NaCu 1 / 9 Ni 2 / 9 Fe 1 / 3 Mn 1 / 3 The O2 positive electrode material, conductive agent Super P, conductive agent CNT, and binder PVDF are dissolved in the solvent NMP according to the mass ratio of 96.5:1.5:0.5:1.5, and stirred evenly at a certain speed. After adjusting to a suitable viscosity, the positive electrode slurry is coated on the aluminum foil; then the positive electrode sheet is obtained through drying, cold pressing, and slitting;

[0085] Preparation of the diaphragm: (1) First, coat the base film with 0.16 g / cm 2PVDF coating to improve the adhesion of the base film; (2) adding NaNO3 to the solvent, stirring and ultrasonicating to obtain a uniform solution. The average particle size of NaNO3 is 500nm, the solution concentration is 0.5mol / L, and the solvent can be preferably deionized water or anhydrous ethanol; (3) immersing the base film of (1) in the above solution (2), repeating 2-5 times, and controlling the content of NaNO3 on the diaphragm to be about 4mg / cm 2 , and then drying the obtained diaphragm.

[0086] Embodiment 16-21:

[0087] By changing some parameters in Example 15, the remaining parameters were the same as in Example 15 to prepare soft pack batteries, wherein the positive electrode active material in Examples 20-21 was NaNi without Cu. 1 / 3 Fe 1 / 3 Mn 1 / 3 O2, and CuF2 was added to the electrolyte. The parameter changes and results are listed in Table 2.

[0088] Comparative Examples 11-14

[0089] By changing some parameters in Example 15, the other parameters were prepared in the same manner as in Example 15; wherein the positive electrode active material in Comparative Example 12 was NaNi free of Cu. 1 / 3 Fe 1 / 3 Mn 1 / 3 O2, and no Cu is introduced into the system; the positive electrode active material in Comparative Example 13 uses NaNi without Cu 1 / 3 Fe 1 / 3 Mn 1 / 3 O2, and CuF2 is added to the electrolyte; the positive electrode active materials CuO and NaNi in Comparative Example 14 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 was compounded at a ratio of 1:9. The parameter changes and results are listed in Table 3.

[0090] Table 3

[0091]

[0092]

[0093] As can be seen from Table 3, as shown in Examples 15-21, the introduction of sodium nitrate as a diaphragm functional additive also shows good electrical performance improvement ability compared to as a negative electrode functional additive. The trend of the cycle results is basically consistent with that of Examples 1-7, and the low-temperature performance can be improved at the same time, which once again confirms the influence of migration on the construction of the interface film. At the same time, it is also found that in terms of the overall effect of improving the cycle performance and low-temperature performance, Examples 15-21 are slightly lower than Examples 1-7, indicating that the migration of sodium nitrate as a diaphragm functional additive also has a slight effect on the construction rate of the interface film. However, sodium nitrate has the advantage of preventing excessive deposition on the diaphragm in the initial stages of the positive and negative electrodes. As shown in Example 19, its cycle performance has not been significantly reduced, and the particle size of sodium nitrate can be applied to a wider range.

[0094] Comparative Example 11 introduced insufficient sodium nitrate into the system, and Comparative Example 12 did not introduce Cu into the system. 2+ , the battery performance is greatly reduced. Comparative Examples 13 and 14 both make Cu 2+ The concentration is greatly increased, but the performance improvement is difficult to achieve.

[0095] The technical features of the above-described embodiments can be combined arbitrarily. In order to make the description concise, all possible combinations of the technical features in the above-described embodiments are not described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification. Although the embodiments of the present invention have been shown and described above, it can be understood that the above-described embodiments are exemplary and cannot be understood as limitations of the present invention. Those of ordinary skill in the art can change, modify, replace and deform the above-described embodiments within the scope of the present invention. In addition, those of ordinary skill in the art can combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples without contradiction.

Claims

1. A sodium ion battery comprising a positive electrode, a negative electrode, an electrolyte and a separator; the positive electrode contains a functional additive sodium nitrate, and the positive electrode active material is a copper-containing layered oxide Na n Cu u M v Ni x Mn y Fe z O2, 0.9≤n≤1.1, 0.05≤u≤0.15, 0≤v≤0.05, 0.1≤x≤0.25, 0.3≤y≤0.4, 0.3≤z≤0.4, 0.9≤u+v+x+y+z≤1.1, M is selected from one or more of Mg, Ca, B, Al, Zr, Ti, W, Mo, Cr, Sr, Y, Cd, Sn, Sb, Ce, Li, K and Ag; an electrolyte containing an ester solvent is used, and the Cu in the electrolyte is 2+ The concentration n satisfies 1ppm<n≤300ppm, and the Cu 2+ and NO3 - The amount ratio N of the substances satisfies 0.01≤N≤0.

2.

2. The sodium ion battery according to claim 1, characterized in that The sodium nitrate forms an inorganic Na-N SEI film in situ on the negative electrode sheet. The inorganic Na-N SEI film contains Na3N and NaN x O y .

3. The sodium ion battery according to claim 1, characterized in that: Cu in electrolyte 2+ The concentration n satisfies 30ppm<n≤200ppm.

4. The sodium ion battery according to claim 1, characterized in that Cu in electrolyte 2+ and NO3 - The amount ratio N of the substances satisfies 0.01≤N≤0.

1.

5. The sodium ion battery according to claim 1, characterized in that: The Cu 2+ It also comes from the electrolyte; Preferably, the Cu 2+ It also comes from copper ion-containing additives in the electrolyte; Preferably, the copper ion-containing additive includes one or more of CuF2, CuFSI, and copper hexafluorophosphate.

6. The sodium ion battery according to claim 1, characterized in that: In the electrolyte containing ester solvents, the ester solvents include one or more of ethylene carbonate, ethylene carbonate, propylene carbonate, dipropyl carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, methylpropyl carbonate, ethylpropyl carbonate, butylene carbonate, methyl formate, ethyl acetate, propyl acetate, propyl propionate, methyl butyrate, ethyl propionate, ethyl butyrate, etc.

7. The sodium ion battery according to claim 1, characterized in that: The average particle size of the sodium nitrate does not exceed 2 μm, preferably 10 nm ≤ D ≤ 1 μm.

8. The sodium ion battery according to claim 1, characterized in that: The mass proportion of sodium nitrate in the positive electrode dissolved in the electrolyte is 0.05% to 0.75%.

9. The sodium ion battery according to claim 1, characterized in that: Sodium nitrate is used as a positive electrode functional additive, and its mass proportion in the positive electrode slurry is 0.1-1.5wt%.

10. The method for preparing a sodium ion battery according to any one of claims 1 to 9, wherein a copper-containing layered oxide is used as a positive electrode active material, and sodium nitrate is added to a positive electrode slurry according to a stoichiometric ratio to prepare a positive electrode sheet, a negative electrode sheet and a separator are added, and an electrolyte is injected to assemble a battery, and the battery is formed.